In this issue - Yamakawa T., Peter (2014)
We are pleased to introduce the 36th issue of the Journal of Economics, Finance and Administrative Science. The journal promotes research in the field of economics, finance, operations, management and supply chain management. The latter fields are typical for the business school. Our purpose is to show the state of the art in research for different business fields. Also, our journal is international oriented with worldwide research. DOI: http://dx.doi.org/10.1016/j.jefas.2014.04.002